A day with the homeless - Mohd Ferdaus, Musa (2017)
Kuala Lumpur, 1st April – 2nd Residential College Student Representative (PEKA 2) together with 1st Residential College Student Representative (PEKA 1) and Kelab Pembimbing Rakan Siswa (PERSIS) organized a “Prihatin Project : A Day with the Homeless” held at Kuala Lumpur Homeless Transit Center.